KONSEP PARIWISATA DAN KOMUNIKASI YANG EFEKTIF - Wulandari, Dwi Pratiwi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Tourism is all activities related to the entry, stay and movement of foreign residents within or outside a particular country, city or region. Communication is often referred to as an information system, namely all elements that are interconnected and cannot be separated in an effort to create, receive and give something to other people with a specific purpose. Process is the stages or steps that are followed in achieving a goal. The communication process is the stages or steps that go through in carrying out communication. Tourism communication develops by combining several scientific disciplines in one study of communication and tourism. Tourism communication studies have a biological closeness to the communication and tourism studies that gave rise to them. Tourism communication is human activities in conveying news and information about trips or visits to an area/tourist attraction. The role of tourism communication can be to achieve promotions or let people know where the best tourism spots are to visit and it can also increase the culture of the community which becomes more familiar and our country's foreign exchange can also increase.